Effect of proton radiation on 8T CMOS image sensors for space applications. Issue 7 (26th July 2021) - Fu, Jing; Feng, Jie; Li, Yu-Dong; Guo, Qi; Wei, Ying; Wen, Lin; Zhou, Dong; Zhang, Xiang; Cai, Yu-Long; Liu, Bing-Kai
ABSTRACT: As mainstream optical imaging electronic devices, image sensors are widely used in space missions under complex radiation environments. This study investigated the effects 60 and 10 MeV proton irradiations on dark current, dark signal non-uniformity (DSNU), and photon response non-uniformity (PRNU) for a commercial global shutter 8T complementary metal–oxide semiconductor (CMOS) image sensor. A fluence range from 9 × 10 9 p/cm 2 to 7.26 × 10 10 p/cm 2 was considered. The total ionizing dose deposited reached 10 krad (Si), which significantly increased the dark current. DSNU and PRNU also followed a similar trend with an increase in the dose, which is based on the effects of the total dose and displacement damage. After irradiation, a TCAD simulation was conducted to identify the radiation-induced defects. The results showed that the trapped positive charges in the oxides, interface states in the Si/SiO2 interface, and bulk defects in a pinned photodiode depleted region significantly increased the dark current. The outcomes of this study form significant reference for advancements in radiation-hardened image sensor designs.